(untitled) (Research, Society and Development, 2021)
The media has strategies that exaggerately appeal to children and young people, profiting more and more from the sale of their products. The study aimed to describe the power of influence that the media exert on the food choices of children and adolescents. This is a bibliographic study, through a literature review with electronic searches. Advertising drives the population to inappropriate food choices, causing health problems. With the increasing prevalence of childhood obesity, measures need to be taken to monitor food marketing. The virtual world has become influential in recent years, also contributing to the behavior of eating disorders. Bad habits obtained in youth can influence dietary performance throughout life, reflecting risk factors for the development of non-communicable chronic diseases and psychological trauma. An effective ban on the dissemination of food products aimed at children is essential to protect their rights, physical, psychological and moral integrity. Finally, it is necessary to reflect on the importance of monitoring advertisements that promote unhealthy foods. In addition, it is essential that everyone is aware of the consequences that obesity can have on the long-term health of children.